Interface structure between Nb thin film and MgO(112) substrate: A first-principles prediction - Yang, Jun; Moh, Pak Yan; Baco, Saturi; Jin, Yongzhong; Fang, Yong; Zong, Hongxiang (Frontiers in Materials, 2023)
The crystal orientation of ceramic substrate is an important factor affecting the interface structure of metal/ceramic composite materials. But there is little information about the interface composed by metal film and ceramic substrate with a high-index plane. In this work, we predicted the interface structure between Nb film and MgO(112) substrate by calculating the interface separation works of different interface models with first-principles calculation method. Results showed the preferred growth direction is Nb[120], and the value of the interface separation work is 0.35 eV/ Å2. The lattice mismatch between the film and substrate is less than three percent, implying a coherent interface type is highly realizable in Nb/MgO(112). Further, we analyzed the interface structures of Nb/MgO(100), Nb/MgO(110), Nb/MgO(111) and Nb/MgO(112), and found the unique atomic configuration of the MgO substrate is the main factor determining the preferred interface structure of Nb/MgO.